Adaptation of the Beck Anxiety Inventory in population of Buenos Aires - Nicolás Alejandro Vizioli; Alejandro Emilio Pagano (Interacciones)
Background: Currently, anxiety disorders are the most prevalent worldwide, reaching a rate of 5% in Argentina in 2017. The Beck Anxiety Inventory (BAI) is one of the instruments most used in research and clinic today. In its construction, one of the objectives was to evaluate anxiety symptoms that are not usually evident in depressive disorders, which is why it is a relevant test to make a differential diagnosis. The objective of this study was to adapt the BAI to the adult population of Buenos Aires. Methods: A direct translation of the inventory and then an expert judgment to assess the content validity were carried out. The discrimination capacity of the items was analyzed and the structural validity of the test was evaluated according to different models found in the literature. Also, the internal consistency of the instrument was analyzed. Results: The adaptation presents adequate content validity and the items have been shown to discriminate adequately. As for the confirmatory factor analyzes, the most parsimonious solution, which indicates the one-dimensionality of the construct, was chosen, providing evidence of construct validity. In turn, the adaptation presents adequate internal consistency. Tentative normative values are offered. Conclusion: Evidence of validity and reliability has been found for the Argentine adaptation of the BAI. It is considered an instrument of great clinical utility.